Help! We have strange powers! [compact disc, unabridged] - Stine, R. L. (Stine, R. L. Goosebumps HorrorLand, 2009)
Jilly and her twin brother, Jackson, are startled when they suddenly discover they can read each other's thoughts. But that's not all, they can read other people's thoughts, too! The strange new powers are exciting at first, but they discover that somebody else knows their secret, somebody who will stop at nothing to control their powers...